VEGF gene +936C/T polymorphism decreases the risk of colorectal cancer - Savabkar, Sanaz; Chaleshi, Vahid; Behboudi Farahbakhsh, Faegheh; Montazer Haghighi, Mahdi; Zali, Neda; Nazemalhosseini Mojarad, Ehsan; Vahedi, Mohsen; Javadi, Gholam Reza; Asadzade Aghdaei, Hamid; Zali, Mohammad Reza (European Journal of Oncology and Environmental Health, 2015)
Background/aims: Vascular endothelial growth factor (VEGF) is a signal protein and plays a main role in angiogenesis and metastasis of tumors. Some variation in 3΄untranslated region (3΄UTR) of VEGF gene could alter the expression of this gene. In this study we have evaluated the possible association between +936C/T (rs3025039) polymorphism located in 3΄UTR of VEGF gene and the risk of colorectal cancer (CRC) in an Iranian population.Methods: In the present case-control study, VEGF genotypes of +936C/T polymorphism were determined in 200 patients with CRC and 200 control individuals. DNA was extracted from blood specimens and genotypes were analyzed by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) method.Results: A significant correlation was found between+ 936C/T variant in the VEGF gene and CRC risk. Frequency of TT genotype was 16% in control and 2% in case study. There was a statistically significant difference in TT genotype frequency between CRC patients and control individuals (adjusted OR= 0.229, 95% CI= 0.058-0.899; P=0.035).Conclusions: These results suggest that TT genotype may have a protective effect against colorectal cancer in an Iranian population.